High-power Er:Y2O3 ceramic laser with an optical vortex beam output at ∼ 2.7 μm - Ding, Manman; Wang, Jun; Wang, Fei; Shen, Deyuan; Tang, Dingyuan; Zhu, Heyuan (Frontiers in Physics, 2023)
We report on the direct generation of the high-power optical vortices at ∼2.7 μm from an Er:Y2O3 ceramic laser end-pumped by an annular pump beam using a simple capillary fiber-based pump beam conditioning scheme. Taking advantage of the thermal gradient on the gain medium and mode matching between the pump and oscillating modes, vortex beams with a controllable topological charge order of l = 1 and l = 2 were successfully achieved. The laser yields 4.65 W of output power at an absorbed power of 19.8 W, corresponding to a slope efficiency of 25.9% with respect to the absorbed pump power. Adaptable beam profiles from a shallow crater-shape to quasi-top-hat intensity patterns were directly produced by actively defining the gain distribution in the ceramic, generating 4-W shallow crater-shape beams and 3.9-W quasi-top-hat beams, corresponding to a slope efficiency of 22.0% and 22.7%, respectively. Such optical vortices and tailored spatial intensity profiles in the 3-µm spectral region will enable novel applications, such as super-resolution molecular spectroscopy and material processing.